ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
The skin provides a model for regenerative medicine, prompting the design of cultured reconstructed tissue substitutes. Translational research and bioengineering have indeed given rise to clinical applications such as the grafting of cultured skin substitutes in severe burn patients, more than four decades ago, and more recently the correction of a genodermatosis by a cell and gene therapy approach. In addition, therapeutic uses of bioengineered skin substitutes are considered for chronic wounds and ulcers, which affect much larger patient populations. This history has given rise to multiple innovations involving original concepts, combined with new methodological and technical approaches. The variables relate to the cell sources used, which may include cells from neonatal or adult skin, autologous or allogeneic, or skin cells obtained by directed differentiation of pluripotent stem cells. They also concern methods and culture protocols used for cell expansion phase in two-dimensional (2D) culture, then the production phase of 3D skin substitutes, a major current challenge being the elimination of constituents not chemically defined and/or of animal origin. By outlining the main technological options, this review aims to guide the design of next-generation skin substitutes that will reconcile biological performance, regulatory expectations and realistic clinical implementation.